EdTech for Special Educational Needs and Disabilities in Malawi: Setting the Research Agenda - Plaut, Daniel; Pitchford, Nicola; Humphrey, Catherine (2024)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

L'utilisation des preuves pour renforcer la formation pédagogique à travers les technologies à Madagascar - Koomar, Saalim; Moss Coflan, Caitlin; Rasolohéry, Hasiniavo (2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodoETH

Sierra Leone Series: the Pikin-to-Pikin Movement and its focus on child protection, education, nutrition and health - McBurnie, Chris; Swaray, Abdulai; Kamara, Bai (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen

Using evidence to strengthen tech-supported teacher professional development in Madagascar - Koomar, Saalim; Moss Coflan, Caitlin; Rasolohéry, Hasiniavo (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _r:AddedByZotZen; _zenodoETH

Expert Consultation: Radio-Based Education in the Philippines - McBurnie, Chris (EdTech Hub, 2020)
These slides present an overview of educational radio programming with a particular focus on quality assurance and content design.
Keywords: C:Philippines; F: Helpdesk response; H:Radio; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v2; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode